2008
DOI: 10.1177/0143831x08093376
|View full text |Cite
|
Sign up to set email alerts
|

Variable Pay and Collective Bargaining: A Cross-National Comparison of the Banking Sector

Abstract: This article analyses the challenge of variable pay to collective bargaining, based on a cross-national comparison that takes banking organizations in Austria, Norway, Spain and the UK as representatives of Europe's principal bargaining systems. The hypothesis is that the capacity of collective bargaining to govern variable pay varies with the bargaining system. As the findings show, articulated multi-employer bargaining is more able to govern variable pay than its unarticulated counterpart and single-employer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…As spelled out in other articles from the project Nergaard et al, 2009a;Traxler et al, 2008), the main advantage of the Norwegian -or Nordic -model in this respect is the two-tier structure of collective agreements, providing a developed arena for company bargaining within a framework of sector agreements and single channel trade union representation. As shown also in other recent comparative studies (Due and Madsen, 2008;Ilsøe et al, 2007;Stokke, 2008), such institutional configurations tend to enable an extent of articulation between local and central trade unions that seems to enhance a level of trust and parity between the local actors that is more rarely seen in the other countries.…”
Section: Discussionmentioning
confidence: 98%
“…As spelled out in other articles from the project Nergaard et al, 2009a;Traxler et al, 2008), the main advantage of the Norwegian -or Nordic -model in this respect is the two-tier structure of collective agreements, providing a developed arena for company bargaining within a framework of sector agreements and single channel trade union representation. As shown also in other recent comparative studies (Due and Madsen, 2008;Ilsøe et al, 2007;Stokke, 2008), such institutional configurations tend to enable an extent of articulation between local and central trade unions that seems to enhance a level of trust and parity between the local actors that is more rarely seen in the other countries.…”
Section: Discussionmentioning
confidence: 98%
“…This may be explained by the ongoing trend of decentralization and hybridization of collective bargaining in the CME context. National level bargaining in CMEs has come under pressure and is increasingly combined with bargaining at lower levels in order to leverage more flexibility in terms and conditions of employment (Traxler, Arrowsmith, Nergaard, & Molins Lopez-Rodo, 2008;Kalmi, Pendleton, & Poutsma, 2012). There is also a significant positive association between national and individual level bargaining in CMEs suggesting more leeway in setting labor terms and conditions individually.…”
mentioning
confidence: 99%
“…In this case we refer to deregulation and decentralisation of agreements, which opens up the possibility for more flexible working and flexible pay practices. Traxler et al (2008) found this result in continental Europe. For Belgium, Rusinek and Rycx (2008) found that pay is more sensitive to performance when wage setting is decentralised.…”
Section: Industrial Relations and The Adoption Of Prpmentioning
confidence: 52%